Genotypic variability in radial resistance to water flow in olive roots and its response to temperature variations. (6th February 2020) - López-Bernal, Á; García-Tejera, O; Testi, L; Villalobos, F J
Abstract: As radial root resistance ( R p ) represents one of the key components of the soil–plant–atmosphere continuum resistance catena modulating water transport, understanding its control is essential for physiologists, modelers and breeders. Reports of R p, however, are still scarce and scattered in the scientific literature. In this study, we assessed genetic variability in R p and its dependence on temperature in five widely used olive cultivars. In a first experiment, cultivar differences in R p at 25 °C were evaluated from flow–pressure measurements in excised roots and subsequent analysis of root traits. In a second experiment, similar determinations were performed continually over a 5-h period in which temperature was gradually increased from 12 to 32 °C, enabling the assessment of R p response to changing temperature. Despite some variability, our results did not show statistical differences in R p among cultivars in the first experiment. In the second, cultivar differences in R p were not significant at 12 °C, but they became so as temperature increased. Furthermore, the changes in R p between 12 and 32 °C were higher than those expected by the temperature-driven decrease in water viscosity, with the degree of that change differing among cultivars. Also, R p at 25 °C reached momentarily in the second experiment was consistently higher than in the first at that same, but fixed, temperature. Overall, our results suggest that there is limited variability in R p among the studied cultivars when plants have been exposed to a given temperature for sufficient time. Temperature-induced variation in R p might thus be partly explained by changes in membrane permeability that occur slowly, which explains why our values at 25 °C differed between experiments. The observed cultivar differences in R p with warming also indicate faster acclimation of R p to temperature changes in some cultivars than others.